The Dependence of The Gravitational Lensing Properties on The Lens And Source Redshifts - Abd Al-Lateef, Hiba Ahmed; Mahdi, Hareth Saad (Iraqi Journal of Science, 2022)
This work aims to investigate the dependence of gravitational lensing properties on the lens redshift and source redshift.The angular diameter distance hereafter referred to as ADD has been determined using two different numerical integral methods, Simpson's rule, and definite integral methods. Both of those two methods gave identical results. In addition, observational data of gravitational Lensing systems have been used to find the most probable value of lens redshift and source redshift. The result showed that the lens redshift and source redshift are more likely to occur in the ranges of zL=0.2-0.6 and zS=1-3, respectively.Einstein radius and the critical surface mass density have been studied for those ranges of lens and source redshift. The result clearly showed that the redshifts and distances affect the lensing properties. This indicates that observations of gravitational lensing can be efficiently used to probe the distances and redshifts.